Peningkatan Pengetahuan Siswa Sekolah Dasar tentang Bahan Tambahan Pangan Berbahaya dengan Metode Eksperimen Laboratorium - Chairunisa Ayu Saputri; Erna Agung Rakhmawati; Charlis Palupi (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2024)
Food Additives in general are to increase the nutritional value of food, improve the aesthetic and sensory value of food and extend the shelf life of food. There is abuse of food additives which can endanger consumers, such as adding borax and formaldehyde to food. This community service activity is an effort to increase elementary school students' knowledge of dangerous BTP using laboratory experimental methods. The results show that there is an increase in students' knowledge of dangerous food additives.